2021
DOI: 10.3389/fneur.2021.712527
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Updates to Thrombectomy: Targets, New Techniques, and Devices

Abstract: Endovascular thrombectomy (EVT) has been validated in several randomized controlled trials in recent years for its efficacy in the treatment of acute ischemic strokes (AIS) and is now the standard of care according to international guidelines. However, in about 20% of EVT procedures, recanalization is not achieved, and over 50% of patients who undergo EVT still do not have good functional outcome. In this article, we provide an extensive review of the latest evidence and developments in the field of EVT, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 113 publications
(115 reference statements)
0
22
0
Order By: Relevance
“…We found that the combined aspiration stentriever in EVT may be associated with mFPE; however, our study might be underpowered, and larger studies are needed. The choice of the initial technique remains uncertain for DMVOs; however, specific devices are being developed 27 for these DMVO, and the rate of FPE will be a critical criteria to assess their efficacy and their complication rate. We did not find an association between the etiology of the clot and the probability of FPE, requiring further study as well.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the combined aspiration stentriever in EVT may be associated with mFPE; however, our study might be underpowered, and larger studies are needed. The choice of the initial technique remains uncertain for DMVOs; however, specific devices are being developed 27 for these DMVO, and the rate of FPE will be a critical criteria to assess their efficacy and their complication rate. We did not find an association between the etiology of the clot and the probability of FPE, requiring further study as well.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of endovascular treatment are beyond doubt, as MTB improves recanalization rates in AIS patients and decreases associated morbidity and mortality 29 , 30 . It is becoming recognized that the use of stent retrievers is associated with vascular injury 31 34 .…”
Section: Discussionmentioning
confidence: 99%
“…To treat AIS caused by intracranial artery obstruction, multimodal treatments, including IV tissue plasminogen activator (t-PA) injection and endovascular treatment techniques, have been developed 10. Among several methods of endovascular treatment, MT using aspiration or a stent retriever has been validated in several randomized controlled trials for its effectiveness in treating AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is it ineffective, but there is also a concern that it may affect the patient’s functional outcome by taking time while performing MT. Recently, there has been a move to nominate a single pass reperfusion standard as the target to achieve during MT 10 19. Furthermore, fewer thrombectomy attempts before rescue stenting were associated with better functional outcomes.…”
Section: Discussionmentioning
confidence: 99%